2015
DOI: 10.5505/turkhijyen.2015.94695
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of nosocomial enterococci by pulsed-field gel electrophoresis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In accordance with our results, polyclonal spread of VRE strains was reported in Tunisia 3 and Australia. 17 In addition, several other studies have reported single clone outbreaks in Turkey 11,13 and Italy. 37 The retrospective, monocentric study design and small sample size constitute our limitations.…”
Section: Dovepressmentioning
confidence: 97%
See 1 more Smart Citation
“…In accordance with our results, polyclonal spread of VRE strains was reported in Tunisia 3 and Australia. 17 In addition, several other studies have reported single clone outbreaks in Turkey 11,13 and Italy. 37 The retrospective, monocentric study design and small sample size constitute our limitations.…”
Section: Dovepressmentioning
confidence: 97%
“…To determine the clonal relationship among isolates, PFGE typing was conducted using a previously described method 11 with some modifications. In brief, the samples were digested with the SmaI restriction enzyme (New England Biolabs) and separated by electrophoresis using the CHEF-DR ® II Pulsed-Field Electrophoresis System (Bio-Rad Laboratories, Nazareth, Belgium) with the following parameters: duration, 20 h; temperature, 14°C; first shot duration, 3.5 s; end shot duration, 23.5 s; shot angle, 120°; and current, 6 V/cm 2 .…”
Section: Detection Of Clonal Relationship Among Isolatesmentioning
confidence: 99%
“…In Turkey, for the first time, vancomycin resistant Enterococcus faecium (VREfae) was isolated from pleural fluid taken from 11-month-old boy with bronchopulmonary infection, empirically treated with vancomycin and amikacin in 1998 by Vural et al (4). In following years, incidence of these microorganisms, especially VREfae, were increasingly reported from different settings and clinical cases in Turkey (5)(6)(7). Although enterococci are known to have intrinsic resistance to certain antimicrobials such as β-lactams, aminoglycosides; recently, vancomycin resistance together with high level of ampicillin and aminoglycoside resistance have frequently been reported, and today is a major cause of concern due to the limited antimicrobial treatment options (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…They stated that the genetic similarity observed between VRE fm isolates suggested that there was cross-contamination in the hospital. In the study of Güldemir D. et al [22]. E. faecium isolates formed one main group and four clusters, and 10 E. faecalis strains formed one major group and three clusters.…”
Section: Discussionmentioning
confidence: 93%